2021
DOI: 10.1177/10901981211038903
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Self-Perception in Oral Health of Pregnant Women

Abstract: Background Health perception is a subjective predictor of long-term morbidity and mortality. Few studies address the perception that pregnant women have of their oral health. Objective The objective of this study was to explore the relationship between socioeconomic factors and self-assessment of oral health in pregnant women from Cali, Colombia. Method A cross-sectional study was carried out with a sample of 998 pregnant women, calculated using the formula to estimate a proportion in finite populations, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
1
3
0
1
Order By: Relevance
“…Specially, it was found that education level was positively influenced the self-reported oral health status, which was similar to the study in South-East Norway [41]. It was also found that income was positively influenced the self-reported oral health status and was similar to the study among Pregnant Women [63]. Finally, it was found in this study that job before retire was also positively associated with self-reported oral health status, which was similar to the previous study [15].…”
Section: The Mediating Effect Of Social Support On the Relationship B...supporting
confidence: 82%
“…Specially, it was found that education level was positively influenced the self-reported oral health status, which was similar to the study in South-East Norway [41]. It was also found that income was positively influenced the self-reported oral health status and was similar to the study among Pregnant Women [63]. Finally, it was found in this study that job before retire was also positively associated with self-reported oral health status, which was similar to the previous study [15].…”
Section: The Mediating Effect Of Social Support On the Relationship B...supporting
confidence: 82%
“…Another explanation for this could be that oral health care instruction for the future baby is not routinely addressed during the mother's prenatal care either because dentists are not part of the prenatal multidisciplinary health team or because there is little interprofessional education [30]. Furthermore, the present study was conducted in a population whose social determinants such as age and educational level may have had a negative influence on the level of knowledge [35][36][37].…”
Section: Discussionmentioning
confidence: 95%
“…Em relação a percepção da saúde bucal pelas gestantes do estudo, a maioria delas está satisfeita relatando ter boa e ótima saúde bucal. Semelhante a pesquisa em que o estado de saúde bucal foi considerado bom por 60,8% das gestantes participantes (Corchuelo-Ojeda et al, 2022). Kabali e Mumghamba (2018) verificaram que grande parte das participantes do estudo realizavam limpeza dentária, 95,6% delas efetuavam a escovação dos dentes duas vezes ao dia, poucas participantes apresentaram complicações periodontais, e as gestantes se identificavam tendo bons hábitos de higiene bucal.…”
Section: Discussionunclassified